The effectiveness of funcional elastic bandagem in fenale pelvic dysfunction: a systematic review of randomized and controlled clinical trials (Research, Society and Development, 2021)
This review aims to gather evidence to identify the effectiveness of funcional elastic bandagem in PADs. Data collection was carried out using the following databases: Medline, Pubmed, Lilacs, SciELO and PEDRO. The PICO acromion was used to define the research questions, with studies of a maximum of 5 years. Nine articles were selected, separated by area. Obstetrics (6), Gynecology (2) and Urogynecology (1) which were within the inclusion criteria for the systematic review.  It was concluded that the Functional Elastic Bandage works effectively in the treatment of female pelvic disorders, promoting good clinical results in relation to anxiety, quality of life and other symptoms associated with PADs.